Media communication and cultural hybridization of digital society - Plenković, Mario (Array, 2020)
The paper is analyzing basic operative terms of visual communication in contemporary digital media environment, which determinates analytical units of media communication and the new culture of communicating and message dissemination. Theory discussion is conducted by diachronic and synchrony analysis of elements of visual communication in digital environment and theory of public action. The main goal is to establish new communicative paradigm of media communication which includes the evaluation of digital skills, media literacy and the characteristics of the new hybrid dig-ital society. Authors observe modern media communication and visual digitalization, not only in technical sense of transmission and adjustment of analog signal into digital signal, but also, simultaneous development of digital culture and adaptation of media content, media production and distribution of content to the new web environment (Web 2.0, Web 3.0, Web 4.0 and theoretical possibilities of so called Web 5.0) de-riving the new contexts of social power.